Analisis Tegangan Bilah Turbin Angin Komposit Berpenguat Spar Ganda - Ikramullah Ikramullah; Hendrix Noviyanto Firmansyah; Djarot Wahju Santoso (Fakultas Teknik, 2023)
The design of wind turbine blades requires structural design and material selection that can withstand aerodynamic loads. The required structural criteria for wind blades are strong and lightweight. Modeling and analysis of stress values were carried out using MSC Patran/Nastran software. The selected material is an E-Glass fiber composite with epoxy resin matrix and has 8 layers with different fiber directions in each layer with fiber direction arrangement [0°/±45°/90°]. The turbine blade model without a spar is compared with the double spar turbine blade. The results found that the stress of the double spar blade had a lower stress value with a maximum tensile stress of 8.83 MPa, while on the blade without spar the maximum tensile stress was 10.6 MPa, while the maximum compressive stress on the double spar blade was 8.68 MPa, the maximum compressive stress on the blade without spar was 11 MPa.